The Global Seismic Moment Rate of Mars After Event S1222a. Issue 7 (6th April 2023) - Knapmeyer, M.; Stähler, S.; Plesa, A.‐C.; Ceylan, S.; Charalambous, C.; Clinton, J.; Dahmen, N.; Durán, C.; Horleston, A.; Kawamura, T.; Kim, D.; Li, J.; et al.
Abstract: The seismic activity of a planet can be described by the corner magnitude, events larger than which are extremely unlikely, and the seismic moment rate, the long‐term average of annual seismic moment release. Marsquake S1222a proves large enough to be representative of the global activity of Mars and places observational constraints on the moment rate. The magnitude‐frequency distribution of relevant Marsquakes indicates a b b ‐value of 1.06. The moment rate is likely between 1.55 × 10 15 N m / a 1.55× 10^15Nm/a and 1.97 × 10 18 N m / a 1.97× 10^18Nm/a, with a marginal distribution peaking at 4.9 × 10 16 N m / a 4.9× 10^16Nm/a . Comparing this with pre‐InSight estimations shows that these tended to overestimate the moment rate, and that 30% or more of the tectonic deformation may occur silently, whereas the seismicity is probably restricted to localized centers rather than spread over the entire planet. Plain Language Summary: The seismic moment rate is a measure for how fast quakes accumulate deformation of the planet's rigid outer layer, the lithosphere. In the past decades, several models for the deformation rate of Mars were developed either from the traces quakes leave on the surface, or from mathematical models of how quickly the planet's interior cools down and shrinks. The large marsquake that occurred on the 4th of May 2022 now allows a statistical estimation of the deformation accumulated on Mars per year, and thus to confront these models with reality. It turns out that, although there is a considerable overlap, the models published prior to InSight tend to overestimate the seismic moment rate, and hence the ongoing deformation on Mars. Possible explanations are that 30% or more of the deformation occurs silently, that is, without causing quakes, or that not the entire planet is seismically active but only specific regions. Key Points: A single large marsquake suffices to constrain the global seismic moment rate Pre‐InSight estimations tended to overestimate the moment rate Either a significant part of the ongoing deformation occurs silent, or seismic activity is restricted to some activity centers, or both